Implementation Of A Literacy Program To Improve The Reading Skills Of Low-Grade Students Of SDN 1 Santong Mulia In The School Year 2025 - Ulfa, Siti Mariah; Hadi, Rusman; Mulyono, Ana (Peneliti.net, 2025)
This study aims to describe the implementation of the literacy program in improving the reading skills of low-grade students at SDN 1 Santong Mulia. This research used a qualitative approach with descriptive methods. Data collection techniques were conducted through observation, interviews and documentation. The research subjects included low-grade teachers, students in grades I and II, and the principal. The results showed that the literacy program is implemented through reading activities 15 minutes before lessons, providing a reading corner in the classroom, reading picture storybooks together, and parents' involvement in accompanying children to read at home. The impact of the implementation of this literacy program can be seen in the increase in students' interest in reading, ability to recognize letters and words, and understanding of the content of simple reading. In addition, students become more active in reading aloud and are able to retell the content of the story. Although there are some obstacles such as limited book collections and limited time for individual assistance, in general the literacy program has made a positive contribution in improving the reading skills of low-grade students. This study recommends that the literacy program continue to be developed and supported by all school parties and parents so that the results achieved can be maximized.